An alkynyltelluronium iodide and its solid state structure: evidence for p→σ* interactions - Werz, Daniel B.; Gleiter, Rolf; Rominger, Frank (Journal of organometallic chemistry, 2004)
The synthesis of the first alkynyltelluronium salt is presented. X-ray investigations of this species reveal a two-dimensional polymeric structure, assembled through various secondary Te⋯Te and Te ⋯I interactions. The structure itself can be rationalized in terms of p→σ* interactions.